Vector mechanics for engineers : - Beer, Ferdinand P. (McGraw-Hill, 1977)
A primary objective in a first course in mechanics is to help develop a student's ability first to analyze problems in a simple and logical manner, and then to apply basic principles to their solutions. A strong conceptual understanding of these basic mechanics principles is essential for successfully solving mechanics problems.